Children’s and adults’ neural bases of verbal and nonverbal ‘Theory of Mind’ - Kobayashi, Chiyoko (2007)
Theory of mind (ToM) - our ability to predict behaviors of others in terms of their underlying intentions - has been examined through verbal and nonverbal false-belief (FB) tasks. Previous brain imaging studies of ToM in adults have implicated medial prefrontal cortex (mPFC) and temporo-parietal junction (TPJ) for adults’ ToM ability. To examine age and modality related differences and similarities in neural correlates of ToM, we tested 16 adults (18-40 years-old) and 12 children (8-12 years-old) with verbal (story) and nonverbal (cartoon) FB tasks, using functional magnetic resonance imaging (fMRI). Both age groups showed significant activity in the TPJ bilaterally and right inferior parietal lobule (IPL) in a modality-independent manner, indicating that these areas are important for ToM during both adulthood and childhood, regardless of modality. We also found significant age-related differences in the ToM condition-specific activity for the story and cartoon tasks in the left inferior frontal gyrus (IFG) and left TPJ. These results suggest that depending on the modality adults may utilize different brain regions from children in understanding ToM.